20 Days Intensive Arabic Language Training To Improve Maharah Al-Kalam As The First Step In Forming Bi'ah 'Arabiyah At Al-Furqon Salafiyah Islamic Boarding School Sawangan Magelang - Surahmat, S; Mawardi, Imam; Anshori, Muchlis (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
Salafiyah Islamic Boarding School (PPS) Al-Furqon Sawangan is an Islamic educational institution under the auspices of the Ministry of Religion which focuses on learning Al- Qur'an tahfidz. This institution also pays more attention to Arabic as the language of the Qur'an. Apart from being a compulsory subject based on the curriculum structure of the Ministry of Religion, PPS Al-Furqon also makes Arabic a superior subject. Various efforts have been taken to form a Bi’ah ‘Arabiyah (Arabic-speaking environment), including by conducting intensive Arabic language training for all pesantren families, both students, teachers and employees. This study uses a descriptive qualitative approach. This study aims to find out how the implementation of intensive Arabic training for 20 days at PPS Al-Furqon Sawangan. The results showed that intensive Arabic language training for 20 days had a positive effect on the Arabic language communication skills of Islamic boarding school students and families.